The Role Of Teachers in Islamic Education - Nur Kholis (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) Institut Agama Islam Negeri (IAIN) Metro, 2021)
This study aims to describe the role of teachers in Islamic education. This research is a literature study with the main source of the Al-Qur'an, Hadith and Scientific Journals. The results showed that the role of the teacher in understanding the characteristics of students is the first thing that must be done to achieve the goals of Islamic education because in this realm a teacher will determine the methods, models and strategies to be used. Teachers in developing lesson plans must pay attention to the curriculum, objectives, activity designs and evaluation models to be used. The stages of classroom management carried out by a teacher must refer to the desired class conditions, analyze existing class conditions, select and use managerial strategies and assess managerial effectiveness and a good physical arrangement of the classroom environment. The positive contribution of this research is to provide information to teachers and the community that the three roles of teachers as mentioned above must be fulfilled in order to maximize the goals of education.